2011
DOI: 10.1002/jcc.21973
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lipid surface area in protein–membrane systems combining voronoi tessellation and monte carlo integration methods

Abstract: All-atom molecular dynamics (MD) simulation has become a powerful research tool to investigate structural and dynamical properties of biological membranes and membrane proteins. The lipid structures of simple membrane systems in recent MD simulations are in good agreement with those obtained by experiments. However, for protein-membrane systems, the complexity of protein-lipid interactions makes investigation of lipid structure difficult. Although the area per lipid is one of the essential structural propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…While it is difficult to estimate the correct number of lipids in each leaflet of protein–membrane systems to avoid a mismatch in lipid packing, it has been suggested that the area per lipid mismatch up to 5% would be tolerable in membrane simulations of typical all-atom system sizes [163]. For the analysis of the area per lipid in protein–membrane systems, the Voronoi tessellation Monte Carlo integration method has been proposed [164], which also makes possible to assess equilibration of lipid bilayers by comparing the obtained area per lipid with the experimental data.…”
Section: Molecular Models For Membranes and Membrane Proteinsmentioning
confidence: 99%
“…While it is difficult to estimate the correct number of lipids in each leaflet of protein–membrane systems to avoid a mismatch in lipid packing, it has been suggested that the area per lipid mismatch up to 5% would be tolerable in membrane simulations of typical all-atom system sizes [163]. For the analysis of the area per lipid in protein–membrane systems, the Voronoi tessellation Monte Carlo integration method has been proposed [164], which also makes possible to assess equilibration of lipid bilayers by comparing the obtained area per lipid with the experimental data.…”
Section: Molecular Models For Membranes and Membrane Proteinsmentioning
confidence: 99%
“…Previous MC-, VT- and grid-based studies on lipid domains and lipid/protein interactions [9, 13, 22, 23] projected the atoms or the center-of-masses of lipids on the bilayer surface or xy -plane. This projection approach might introduce uncertainties in the lipid classification and averages out atomistic detail about the structure of the protein-lipid bilayer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous simulation studies on pure lipid bilayers have demonstrated that the time-averaged volume and surface area per lipid, membrane thickness, order parameter, and domain size of the bulk lipids compared favorably with those from experiments [1221]. In the presence of protein, different analytical tools based on the grid-method [22], Voronoi tessellations (VT) [2], Monte Carlo (MC) Integration [10] and hybrid VT and MC integration [23] have been proposed to study protein/lipid interactions. In most cases, a two-dimensional projection of the protein and lipid atoms or molecules on the bilayer plane was used to classify the annular and non-annular lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Mori and colleagues proposed a more sophisticated method for calculating the APL using Voronoi tessellation and Monte Carlo simulation [80]. Coordinates of center of mass for each lipid molecules and coordinates for protein atoms located between the maximum and minimum z-coordinates for the monolayer are projected onto the XY plane.…”
Section: Tools For Membrane MD Simulation Analysismentioning
confidence: 99%